Quality Analysis of Service Load Balancing Using PCC, ECMP, and NTH Methods - Kurnianto Tri Nugroho; Bagus Julianto; Dhodit Rengga Tisna; Danny Febryan Nur M S (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2023)
One of the solutions to wede168 get a better quality of internet service is to utilize load balancing technology. We can use more than one different ISP (Internet Service Provider) which is then balanced with load balancing technology, where this technique is used to distribute the traffic load on two or more connection lines in a balanced way so that traffic can run optimally, maximizing throughput, minimizing response time. and avoid overload on any of the connection lines. This study aims to determine the comparison of Quality of Service load balancing with the PCC, ECMP and NTH methods on Mikrotik. The test method uses the web application www.speedtest.cbn.id, www.fast.com (1 connection), the results will show ping, download speed, upload speed, and monitoring from the Mikrotik router side. The research stages used the Network Development Life Cycle method, namely analysis, design, prototype simulation, implementation, monitoring and management. The results of the research are in the form of a performance comparison between load balancing on 2 internet lines using the PCC, ECMP and NTH methods on the proxy router. Based on the tests carried out as a whole the load balance using the ECMP method is superior and more reliable in terms of failover effects.